2010
DOI: 10.1007/s00726-010-0511-9
|View full text |Cite
|
Sign up to set email alerts
|

The effect of acidic residues and amphipathicity on the lytic activities of mastoparan peptides studied by fluorescence and CD spectroscopy

Abstract: Some mastoparan peptides extracted from social wasps display antimicrobial activity and some are hemolytic and cytotoxic. Although the cell specificity of these peptides is complex and poorly understood, it is believed that their net charges and their hydrophobicity contribute to modulate their biological activities. We report a study, using fluorescence and circular dichroism spectroscopies, evaluating the influence of these two parameters on the lytic activities of five mastoparans in zwitterionic and anioni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
50
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 29 publications
2
50
0
1
Order By: Relevance
“…This issue is intended to present snapshots of the peptides identified as toxins/ defensins and to explore the diversity of biological systems, novel structures, and the mechanisms of action. The reviews and original manuscripts in this issue focus on peptides from insects Leite et al 2010), spiders Rodríguez et al 2010;Santos et al 2010), amphibians Libério et al 2010;Meneses et al 2010), and humans (Corrales-Garcia et al 2010) by using spectroscopic strategies for the detection, structural elucidation De Souza et al 2010;Leite et al 2010), and characterization of the molecular interactions with biological membranes Zhou et al 2010). Some of the contributions focus on the studies of the structure-activity relationship to achieve a better understanding of the mechanisms of the action .…”
mentioning
confidence: 99%
“…This issue is intended to present snapshots of the peptides identified as toxins/ defensins and to explore the diversity of biological systems, novel structures, and the mechanisms of action. The reviews and original manuscripts in this issue focus on peptides from insects Leite et al 2010), spiders Rodríguez et al 2010;Santos et al 2010), amphibians Libério et al 2010;Meneses et al 2010), and humans (Corrales-Garcia et al 2010) by using spectroscopic strategies for the detection, structural elucidation De Souza et al 2010;Leite et al 2010), and characterization of the molecular interactions with biological membranes Zhou et al 2010). Some of the contributions focus on the studies of the structure-activity relationship to achieve a better understanding of the mechanisms of the action .…”
mentioning
confidence: 99%
“…The substitution of aspartic acid (Asp) by an asparagine residue increases its net charge to +3. The increase in the net charge improved the leakage efficiency in anionic mixed LUVs and GUVs (Dos Santos Cabrera et al 2011;Leite et al 2011). The net charge of peptides concomitantly containing acidic and basic residues, Asp and Lys like MP1 and L1A, can be modulated by changes in the pH of the solution.…”
Section: Charge Effect On the Affinity And Lytic Activity Of Peptidesmentioning
confidence: 99%
“…Results showed that Polybia-MP-1 is highly selective for bacterial cells; its lytic activity is characterized by a threshold peptide-to-lipid molar ratio that depends on the phospholipid composition of the vesicles. The same studies suggest that mastoparan analogs accumulate on the bilayer surface and induce a transient interruption to its barrier properties, leaking the vesicle contents [24][25][26].…”
Section: Introductionmentioning
confidence: 98%
“…Considering the wide therapeutic applicability of the mastoparans and extremely reduced number of side effects [21][22][23][24][25][26], the design and synthesis of new mastoparan derivatives appear to be a necessity in preclinical and clinical studies. On the other hand, limited knowledge about the mastoparan mechanism of action at the pathogen membranes requires application of methods by which the antimicrobial activity of new derivatives of mastoparan can be calculated without requiring the presence of microbial membranes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation